2011
DOI: 10.1111/j.1755-3768.2010.02097.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the effectiveness between amniotic membrane homogenate and transplanted amniotic membrane in healing corneal damage in a rabbit model

Abstract: ABSTRACT.Purpose: To determine whether amniotic membrane homogenate is as effective in healing corneal damage as amniotic membrane transplantation in a rabbit model. Method: The rabbits were divided into three groups. The cornea of one eye in each rabbit was incised resulting in a defect of approximately 8 mm in diameter. Amniotic membrane transplantation was performed in the first group, and amnion homogenate was administered four times a day in the second group. The third group was the control group. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 17 publications
1
46
1
2
Order By: Relevance
“…Some studies revealed interesting results concerning homogenates. 9,10,12 Based on a mouse model, our study presented similar results when comparing the mechanical effect to the biological effect.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Some studies revealed interesting results concerning homogenates. 9,10,12 Based on a mouse model, our study presented similar results when comparing the mechanical effect to the biological effect.…”
Section: Discussionsupporting
confidence: 65%
“…9,12,13 However, transplantation of AMs involves a substantial risk of the following complications: subconjunctival hemorrhage, early degeneration of the membrane, surface infection, and calcification. 8 Recently, Guo et al 10 compared the efficacy of AM homogenates and transplanted AM for the treatment of alkali burns in rabbits and found that amnion homogenates are as effective as transplanted AM in promoting corneal healing.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, using a rabbit model of corneal damage, Guo et al. have demonstrated that during a 7‐day follow‐up, AM homogenates displayed a damage‐reducing effectiveness similar to that of regular amnion grafts …”
Section: New Directionsmentioning
confidence: 99%
“…[5][6][7][8] Depending on the gravity of the corneal injury, different clinical strategies are proposed, ranging from drug treatments that control inflammation and enhance reepithelialization to the use of amniotic patches in more severe cases. [9][10][11][12][13][14] A better molecular understanding of the different steps in corneal wound healing is still needed. In this context, the receptor for advanced glycation end products (RAGE), identified in 1992 by Neeper et al, is a target of interest because of its involvement in the control of gene transcription during inflammation and reepithelialization processes.…”
mentioning
confidence: 99%